PENERAPAN TEKNIK ETL PADA KOMENTAR APLIKASI FLIP.ID DI APLIKASI PLAYSTORE DENGAN APLIKASI PENTAHO - Alif, Rahmat Istighfaroni; Idhom, Mohammad; JS, Wahyu Syaifullah (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
User comments on the Play Store are crucial sources for developers to understand user feedback on their applications. In this research, we introduce the application of Extract, Transform, Load (ETL) Technique to analyze user comments on the Flip.id application on the Play Store using the Pentaho application. The ETL method is utilized to extract comment data, transform it into a suitable format, and load it into a data warehouse for further analysis. This process involves systematic and structured data processing steps. We identify common patterns in user comments to gain valuable insights for application developers in enhancing the quality and user experience of their applications. The research findings indicate that the application of ETL Technique using the Pentaho application can be an effective approach for analyzing user comments on the Play Store platform, as well as providing valuable insights for application developers for data-driven decision-making. This research can serve as a foundation for further research in sentiment analysis and user-driven product improvement